Measuring optic nerve head perfusion to monitor glaucoma: a study on structure-function relationships using laser speckle flowgraphy - Calzetti, Giacomo (2022)
We aimed to describe the global and localized correlations among visual field (VF) sensitivity, optic nerve head (ONH) perfusion measured by laser speckle flowgraphy (LSFG) and neural structure measured by optical coherence tomography (OCT) in open-angle glaucoma (OAG) and to compare the floor effect for LSFG and OCT.